Pengaruh E-Promotion Fintech terhadap Niat Penggunaan: Studi Kasus Pengguna SPayLater di Kota Bandung - Giovanni Azel; Ermina Tiorida; Sri Raharso (Jurnal Riset Bisnis dan Investasi, 2026)
The rapid development of financial technology (fintech) in Indonesia has led to the significant growth of Buy Now Pay Later (BNPL) services, with SPayLater emerging as one of the leading providers actively utilizing digital promotion strategies. This study aims to examine the effect of e-promotion on users’ intention to use the SPayLater service in Bandung City. A quantitative research design with descriptive and causal approaches was employed. Data were collected through an online questionnaire administered to 130 active SPayLater users selected using purposive sampling. The research instrument was tested and confirmed to be valid and reliable, with a Cronbach’s Alpha value of 0.825. Descriptive statistical analysis indicates that both e-promotion and intention to use are perceived at good to high levels. The results of simple linear regression analysis reveal that e-promotion has a positive and significant effect on intention to use (β = 0.109; p < 0.001), with a coefficient of determination (R²) of 0.210. These findings suggest that e-promotion contributes to enhancing users’ intention to use SPayLater, although a substantial proportion of the variance is explained by other factors beyond the research model. Furthermore, two-way communication in digital promotion is identified as the most effective promotional dimension. This study recommends that service providers strengthen interactive and informative e-promotion strategies, while regulators enhance digital financial literacy initiatives to support the sustainable use of BNPL services.